Modelling the egg components and laying patterns of broiler breeder hens - Ferreira, Nayara T. [UNESP]; Sakomura, Nilva K. [UNESP]; De Paula Dorigam, Juliano César [UNESP]; Da Silva, Edney Pereira [UNESP]; Gous, Robert M. (CSIRO Publishing, 2016)
There is scant information about the reproductive process in broiler breeders, with which to develop a feeding strategy that will be economically optimal for these birds. This study aimed to model the egg production of a flock of broiler breeder hens, using non-isometric equations. The number of eggs produced by 60 broiler breeder hens aged 24-60 weeks was monitored, as was the weight of these eggs and the weights of the components, yolk, albumen and shell. Oviposition sequences and the number and length of pauses between sequences were analysed. Non-isometric functions were applied to predict the weight of the egg; yolk weight was predicted from the age of the hen, while albumen and shell weights were predicted from yolk weight; and egg weight was obtained by summing the component weights. The incidence of soft-shelled and double-yolk eggs was also determined. Yolk weight (YW, g) can be described as YW ≤ 18.03 × (1 - e-0.015 × (t - 103.4)) × e(0.001 × t), where t is the age of the bird (days). The weights of albumen (AW) and shell (SW) were based on YW predictions as follows: AW ≤ 14.38 × YW0.375 and SW ≤ 0.358 × (YW + AW)0.687. The rate of double-yolk egg (DY) production is described by DY ≤ 2.28 × e(0.209 × TFE), and the rate of soft-shelled egg (SS) production by SS ≤ 1.126 + 0.148/(1 - 0.024 × TFE) - 0.056 × TFE, as a function of time from first egg (TFE). On the basis of the results obtained, the model developed here is an accurate reflection of the changes that occur in the number of eggs produced by broiler breeders, as well as in the egg itself and in its components over the entire laying period. This model can thus be used in predicting the nutrient requirements of individual broiler breeder hens, which, when combined with simulated data from a large number of individuals, will accurately describe the laying performance of a flock of broiler breeders.
Keywords: abnormal egg; egg composition; egg production